Digital horticulture: Artificial intelligence revolutionizing plant disease detection for healthier harvests - Singh, Raghuveer; Kangjam, Valenta; Angami, T; Sharma, Susheel Kumar (Indian Horticulture, 2026)
Artificial Intelligence (AI) has become a powerful tool in the field of plant disease detection, offering numerous benefits for improving horticultural practices and ensuring food security. AI techniques, particularly machine learning (ML) and deep learning (DL) along with internet of things (IoT), can help in the early detection and diagnosis of plant diseases, leading to timely and effective disease management practices.